ФОТОЭЛЕКТРИЧЕСКИЕ И ОПТИЧЕСКИЕ СВОЙСТВА КРЕМНИЯ С БИНАРНЫМИ СОЕДИНЕНИЯМИ АТОМОВ ФОСФОРА И ГАЛЛИЯ - Зикриллаев, Н.Ф.; Исамов, С.Б.; Курбанова, У.Х.; Уракова, Ф.Э.; Сатторов, А.А. (SCIENCE and SOCIETY, 2024)
Studies of photoelectric and optical properties of silicon with binary compounds of impurity phosphorus and gallium atoms have shown that their photoelectric and optical parameters are very different from the original silicon. The results of the study of photoelectric and optical properties of the obtained silicon samples showed that new elemental cells and nanoclusters are formed in silicon based on binary compounds of phosphorus and gallium atoms. These formed binary compounds can be considered as new nano-objects in which dimensional quantization can be observed.